2012
DOI: 10.1200/jco.2011.37.1286
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine, But Not Fludarabine, Added to Daunorubicin and Cytarabine During Induction Prolongs Survival of Patients With Acute Myeloid Leukemia: A Multicenter, Randomized Phase III Study

Abstract: The addition of cladribine to the standard induction regimen is associated with increased rate of complete remission and improved survival of adult patients with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 39 publications
8
164
1
2
Order By: Relevance
“…In the subsequent study, they compared 3 arms, 2 of them adding cladribine or fludarabine. In this study, they again showed the addition of cladribine (but not fludarabine) to be associated with significantly higher CR (67.5% versus 56%; p 5 0.001) and 3-year survival rates (45% versus 33%; p 5 0.02) [88].…”
Section: Younger Patients With Amlsupporting
confidence: 55%
“…In the subsequent study, they compared 3 arms, 2 of them adding cladribine or fludarabine. In this study, they again showed the addition of cladribine (but not fludarabine) to be associated with significantly higher CR (67.5% versus 56%; p 5 0.001) and 3-year survival rates (45% versus 33%; p 5 0.02) [88].…”
Section: Younger Patients With Amlsupporting
confidence: 55%
“…CR was more common with DAC than DA (68% vs. 56%) as was CR after the first course (62% vs. 51%), reflecting less resistance and translating into improved survival despite similar CR duration (Fig. 6) [38]. The effect of cladribine was most obvious in patients age 50-60 with "unfavorable" cytogenetics and seemed independent of HCT.…”
Section: Worse Prognosis Patientsmentioning
confidence: 97%
“…6 The safety and efficacy of modified induction chemotherapy or preparative regimen for elderly patients need to be validated. [18][19][20][21][22][23][24][25] We found that decreases in GVHD-related and infection-related mortality contributed to the reduced risk of NRM. These findings are consistent with prior reports.…”
Section: Discussionmentioning
confidence: 75%